2015
DOI: 10.1016/j.ijid.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and recurrent urinary tract infections in premenopausal women: a retrospective study

Abstract: Obesity was found to be associated with RUTIs in premenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
4
17
1
1
Order By: Relevance
“…17 Immune-system deregulation owing to low adiponectin levels-which alters cytokine production by leukocytes-plus natural killer cell cytotoxicity was proposed as a possible mechanism underlying this association. 18 Nonetheless, a similar rate of postoperative UTI was observed for the two groups in the present study. Furthermore, the ABBREVO procedure was found to be a safe and efficient procedure for use among patients characterized as obese.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…17 Immune-system deregulation owing to low adiponectin levels-which alters cytokine production by leukocytes-plus natural killer cell cytotoxicity was proposed as a possible mechanism underlying this association. 18 Nonetheless, a similar rate of postoperative UTI was observed for the two groups in the present study. Furthermore, the ABBREVO procedure was found to be a safe and efficient procedure for use among patients characterized as obese.…”
Section: Discussionsupporting
confidence: 84%
“…Obesity is potentially associated with UTI, with a hazard ratio of 1.25 reported for obese women versus those of normal weight . Immune‐system deregulation owing to low adiponectin levels—which alters cytokine production by leukocytes—plus natural killer cell cytotoxicity was proposed as a possible mechanism underlying this association . Nonetheless, a similar rate of postoperative UTI was observed for the two groups in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…In addition to drug resistance, obesity also increases the risk of RUTIs infection in women. One study revealed significant correlation of obesity with RUTIs (p<0.001) where fatness increases the risk of recurrent infections in women by 27% and drug resistance by 20% (32). In present study, the association between weight and drug resistance also significant compared to other variables.…”
Section: Discussionsupporting
confidence: 59%
“…Many other factors have been thought to predispose women to RUTIs, such as voiding patterns pre-and post-coitus, wiping technique, wearing tight undergarments, deferred voiding habits and vaginal douching; nevertheless, there has been no proven association [304]. Obesity was found to be associated with RUTIs in premenopausal women [305]. Several other risk factors are associated with cystitis, a prior UTI, vaginal infection, diabetes, and genetic susceptibility [306].…”
Section: Recurrent Urinary Tract Infectionsmentioning
confidence: 99%